2016
DOI: 10.1177/1758573216647898
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated rehabilitation after arthroscopic Bankart repair in professional footballers

Abstract: Background: Advances in arthroscopic surgery have resulted in biomechanically stronger repairs that might allow for accelerated rehabilitation protocols and hence faster return to play. Evidence for such regimes in the shoulder, particularly in elite athletes, is lacking. Methods: This prospective single surgeon (PB) series included 34 professional footballers undergoing an accelerated rehabilitation programme following arthroscopic soft tissue stabilization subsequent to traumatic anterior shoulder dislocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 32 publications
0
62
0
14
Order By: Relevance
“…21 Recent data have suggested that overall outcomes are improved in this setting by treating these patients with an arthroscopic soft tissue procedure. [21][22][23][24] Therefore, the continued increase in Bankart repairs performed may represent a more aggressive approach by surgeons in treating patients with primary shoulder dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent data have suggested that overall outcomes are improved in this setting by treating these patients with an arthroscopic soft tissue procedure. [21][22][23][24] Therefore, the continued increase in Bankart repairs performed may represent a more aggressive approach by surgeons in treating patients with primary shoulder dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…gradual recovery, using hydrokinesistherapy also. In the later stages of rehabilitation time and during the game, kinesiotaping was used 6 . It was very important both avoid external rotation in the early stages and recover, as soon as possible, sports specific gestures (active and passive), so that the normal range of motion and muscle strength could be recovered.…”
Section: Original Articlementioning
confidence: 99%
“…The incidence of injury in connection with these two shoulder pathologies is 1.25 per 1000 hours of training and competition, while both pathologies present a high injury recurrence rate. In players under the age of 25 suffering a traumatic anterior shoulder dislocation for the first time, the risk of recurrence is 90-95% when no surgical treatment is carried out [6].…”
Section: Introductionmentioning
confidence: 99%